Ease of Access to Proof of Land Ownership as a Principle of Information Disclosure - Khotbatul Laila (Jurnal Cakrawala Hukum, 2023)
Ease of access to excerpts of the letter C land book as proof of ownership of land rights by the village government in the framework of public information disclosure is urgently needed at this time in order to reduce legal conflicts over land disputes. The research method uses empirical legal research with a sociological juridical approach. The results of the research show that the village government is guided by the provisions of the applicable laws and regulations. The village government publishes a description of the history of the land based on the letter C book in the village to be given to the applicant provided that the applicant is a party that has a legal relationship with the object for which letter C is requested. Obstacles faced by the village government in providing easy access to excerpts from letter C as proof of ownership of land rights in order to realize public information disclosure and an alternative solution, namely the disorganization of village administration, especially in the village letter C book.How to cite item: Laila, Khotbatul. â€œEase of Access to Proof of Land Ownership as a Principle of Information Disclosure.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023):Â 177-188. DOI: doi.org/10.26905/idjch.v14i2.10910.